Post a New Question

maths

posted by on .

f(x)=ln(e^x-e^-x), x>0

By applying in turn the Composite and Quotient Rules, find derivative and second derivative.

Thanks.

  • maths - ,

    f '(x) = (e^x + e^-x)/(e^x - e^-x)
    = e^-x(e^(2x) + 1)/(e^-x(e^(2x) - 1)
    = (e^(2x) + 1)/(e^(2x) -1)

    now use the quotient rule to get the second derivative,
    let me know what you got.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question